2018
DOI: 10.1016/j.gaceta.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the prevalence of diagnosis of overweight-obesity in Spanish children according to the diagnostic criteria set used

Abstract: The prevalence of overweight and obesity varies significantly according to the criteria used to define overweight and obesity. The percentiles of the Foundation Orbegozo gave the lowest estimates and the standards of growth of the World Health Organization were higher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…The prevalence of overweight (including obesity) in our study population based on WHO, CDC and IOTF references was almost similar, 29.6%, 27.4% and 27.6%, respectively, but with differences between the overweight and obesity classification using these references. A higher prevalence of overweight in boys was found in almost all other studies [ 11 , 19 , 32 , 33 ]. Regarding age, the trend was similar no matter the reference used: excess weight prevalence was highest in children before puberty (up to 10–12 years) and lowest in adolescents aged 17–18 years.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The prevalence of overweight (including obesity) in our study population based on WHO, CDC and IOTF references was almost similar, 29.6%, 27.4% and 27.6%, respectively, but with differences between the overweight and obesity classification using these references. A higher prevalence of overweight in boys was found in almost all other studies [ 11 , 19 , 32 , 33 ]. Regarding age, the trend was similar no matter the reference used: excess weight prevalence was highest in children before puberty (up to 10–12 years) and lowest in adolescents aged 17–18 years.…”
Section: Discussionmentioning
confidence: 61%
“…In WHO references, a BMI of 30 kg/m 2 at the age of 18–19 years correspond to a 2SD from the median of the reference population (97.5 th percentile), while in IOTF reference a BMI of 30 kg/m 2 at age 18 years corresponds to the 98.7 th percentile in girls and 98.9 th percentile in boys. There is no consensus on which reference set is the best one: IOTF and CDC references classified fewer children as overweight and obese than the WHO reference [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A pesar de haber cierta evidencia que establece mayor obesidad y sobrepeso en chicas que en chicos, es muy escasa y no se relaciona con estudios españoles (Wang et al, 2014). La evidencia relacionada con España coincide con el presente estudio en afirmar que los chicos adolescentes presentan mayores niveles de sobrepeso y obesidad que las chicas (Bazán et al, 2017;Inchley et al, 2017).…”
Section: Discussionunclassified
“…In this article we present the prevalences of the different levels of obesity according to two of the most widely accepted criteria: the WHO and the IOTF. Other studies have demonstrated differences in prevalences depending on the criteria used [ 25 ]; as such we present both to allow for better comparison with other studies and countries or regions. However, as the aim of this paper was not to compare in detail the two standards but rather to provide objective data on the prevalence of overweight and obesity as defined by the WHO standards, the main results will be presented using the WHO standards.…”
Section: Methodsmentioning
confidence: 99%